Post-entrapment genome engineering: First exon size does not affect the expression of fusion transcripts generated by gene entrapment - Osipovich, Anna B.; Singh, Aparna; Ruley, H. Earl

(untitled) (Genome Research, 2005)
Gene trap mutagenesis in mouse embryonic stem cells has been widely used for genome-wide studies of mammalian gene function. However, while large numbers of genes can be disrupted, individual mutations may suffer from limitations due to the structure and/or placement of targeting vector. To extend the utility of gene trap mutagenesis, replaceable 3′ [or poly(A)] gene trap vectors were developed that permit sequences inserted in individual entrapment clones to be engineered by Cre-mediated recombination. 3′ traps incorporating different drug resistance genes could be readily exchanged, simply by selecting for the drug-resistance gene of the replacement vector. By substituting different 3′ traps, we show that otherwise identical fusion genes containing a large first exon (804 nt) are not expressed at appreciably lower levels than genes expressing small first exons (384 and 151 nt). Thus, size appears to have less effect on the expression and processing of first exons than has been reported for internal exons. Finally, a retroviral poly(A) trap (consisting of a RNA polymerase II promoter, a neomycin-resistance gene, and 5′-splice site) typically produced mutagenized clones in which vector sequences spliced to the 3′-terminal exons of cellular transcription units, suggesting strong selection for fusion transcripts that evade nonsense-mediated decay. The efficient exchange of poly(A) traps should greatly extend the utility of mutant libraries generated by gene entrapment and provides new strategies to study the rules that govern the expression of exons inserted throughout the genome.